The analysis of figurative language in Bohemian Rhapsody’s lyric by Queen - Octa Pratama Putra; Herlin Widasiwi Setianingrum; Sufi Alawiyah; Fitriyah; Juniato (Mitra Palupi, 2020)
Background: Throughout the lyric, -from music- there must be emblazoning with the meaning within it. Purpose: This study is coincided in seeking out the use of figurative language’s content in Bohemian Rhapsody’s lyric by Queen. Design and methods: Whereupon, the qualitative approach with design of content analysis is used in this study. The researcher acts as the main instrument since analyzing it. The focus on this study shows twenty figurative languages usage in it. The entire data is analyzed through three stages; 1). Data reduction, 2). Data representation, 3). Conclusion. Results: The result of this study shows there are 20 kinds of figurative languages; they are; Alliteration (3 lines), assonance and consonance (1 line), Hyperbole (1 line), Imagery (2 lines), Internal rhyme (1 line), Irony (1 line), metaphor (2 lines), and Onomatopoeia (1 line) Personification (1 line), Repetition (1 line), Simile (1 line), and symbolism (two lines). The researcher concludes, the figurative language used by this lyric is to bring the meaning coming up with beautiful language.